2006
DOI: 10.1111/j.1469-7580.2006.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and intermuscular variation in human quadriceps femoris architecture assessed in vivo

Abstract: Despite the functional importance of the human quadriceps femoris in movements such as running, jumping, lifting and climbing, and the known effects of muscle architecture on muscle function, no research has fully described the complex architecture of this muscle group. We used ultrasound imaging techniques to measure muscle thickness, fascicle angle and fascicle length at multiple regions of the four quadriceps muscles in vivo in 31 recreationally active, but non-strength-trained adult men and women. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
459
1
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(505 citation statements)
references
References 70 publications
(166 reference statements)
25
459
1
20
Order By: Relevance
“…These characteristics indicate that rectus femoris muscle may play a substantial role in the achievement of high knee joint velocity. However, due to the complexity of the muscular geometry of rectus femoris, muscle fascicle tracking during dynamic contractions of this muscle represents a technical challenge (Blazevich et al 2006;Massey et al 2015). Regardless of this, we are confident that the vastus lateralis shortening velocity is the most representative of all knee extensors muscles behaviour.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics indicate that rectus femoris muscle may play a substantial role in the achievement of high knee joint velocity. However, due to the complexity of the muscular geometry of rectus femoris, muscle fascicle tracking during dynamic contractions of this muscle represents a technical challenge (Blazevich et al 2006;Massey et al 2015). Regardless of this, we are confident that the vastus lateralis shortening velocity is the most representative of all knee extensors muscles behaviour.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…This required using an extrapolation of the visible part of the fascicle to estimate the whole length according to aponeuroses Blazevich et al 2006). However, Finni et al (2003) showed a relatively small error measurement, ranging between 2 and 7% of the vastus lateralis.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two disposable electrodes 3 mm in diameter were placed over the VL at a center-to-center distance of 2 cm, after shaving and cleaning the skin with alcohol to ensure appropriate contact. 2 The EMG electrodes were placed on the distal portion of the VL, just distal to the ultrasound transducer. This placement of the electrodes likely decreased the absolute EMG signal compared to a placement closer to the center of the VL.…”
Section: Methodsmentioning
confidence: 99%
“…2 Physical Therapist, Cleveland Clinic, Sports Health and Orthopaedic Rehabilitation, Cleveland, OH. 3 Physical Therapist, Ohio University Therapy Associates, Athens, OH.…”
mentioning
confidence: 99%